On Theoretical and Practical Path of Industry-education Integration Community Empowering Tourism Management Talents Cultivation: Based on Perspective of Symbiosis Theory - He, Jianbo; Zhou, Rong (International Journal of Global Economics and Management, 2025)
In the context of the booming development of culture and tourism industry and the reform of vocational education, the industry-education integration community is crucial to the cultivation of talents of tourism management major. Based on symbiosis theory, we analyze the theoretical logic of industry-education integration community empowering talent cultivation, discuss the construction strategies from the organizational, motivational, behavioral and cultural levels, and put forward the practical paths of perfecting the operation mechanism, creating diversified faculty, developing practical curriculum system, and building practical training base by the school and enterprise, aiming to improve the quality of talents cultivation to meet the demands of industry.